PENGARUH CITRA, KUALITAS JASA, DAN PROMOSI TERHADAP KEPUTUSAN KONSUMEN (Studi Pada Primagama Sooko, Mojokerto) - LUCYANA, WITA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
This study is motivated by the increasing number of services tutoring agencies . This was followed by education needs of service users are ever increasing . By the expectation of using appropriate educational services , consumers should be more selective in choosing the type of tutoring agencies . Famous image is the consideration factor for the consumer , followed by quality services and promotions . In accordance with the willing of Primagama consumers is one alternative tutoring agencies are interested in Mojokerto. As a pioneer, Primagama still exist now . Therefore, this study was conducted to determine how the variables influence brand image , quality of services, and promotion of their purchasing decision. Data were collected use questionnaire method against 146 respondents learners of Primagama Sooko outlets, Mojokerto obtained by using non- probability sampling technique. Then conducted an analysis of data obtained using multiple linear analysis. This analysis includes : validity test, the classic assumption test, multiple regression analysis, hypothesis testing by using t test and f test. Hypothesis testing using t-test showed that the three independent variables studied were variable are brand image , quality of services , and the promotion proved positive and significant effect on the dependent variable purchase decision. Then from the F test can be seen that the four independent variables is feasible to test the dependent variable purchase decision. Figures Adjusted R square of 0.643 showed 64.3 per cent of the purchase decision variables can be explained by three independent variables in the regression equation. While the remaining 35.7 percent is explained by other variables outside of the three variables used in this study. Keywords : Decision purchase , image , service of quality , Promotion